INITIAL GROWTH OF Araucaria angustifolia ROOTSTOCK IN RESPONSE TO FERTILIZATION WITH NITROGEN, PHOSPHORUS AND POTASSIUM - Constantino, Valdeci; Motta, Antonio Carlos Vargas; Barbosa, Julierme Zimmer; Dolinski, Marcos Antonio; Zanette, Flavio; Prior, Stephen Arthur (Floresta, 2018)
The objective of this study was to evaluate N, P and K requirements for initial growth of A. angustifolia, as well as symptoms of nutritional deficiency. Three experiments were conducted to evaluate growth response of the species to N, P and K application. Five rates of each element were tested individually. P and K were applied once by mixing with soil before transplanting seedlings, and N was divided into three applications. Six-month-old seedlings (20 cm height) were transplanted into pots containing 16 dm-3 of soil. The response to nutrient applications was monitored by measuring plant height and basal diameter for 16 months. At the conclusion of the experiment, seedling dry mass (roots, needles, branches, and stem), seedling quality index, and nutritional deficiency symptoms were evaluated. Chlorophyll relative index (CRI) and needle color were also measured in the N experiment. Increased plant quality was only observed for N (up to 1.238 mg dm-3) and P fertilization (up to 472 mg dm-3). Small needles, chlorotic, and premature death of lower branches were the main symptoms for N deficiency, while dark green needle coloration, sparse secondary branches, and short internodes characterized P deficiency. Results suggest that nursery applications of N and P are required to improve the growth and quality of plants.